FACTORS AFFECTİNG THE EFFECTİVENESS OF BUDGET MANAGEMENT IN A CASE OF THE MİNİSTRY OF FİNANCE AND ECONOMİC COOPERATİON OF ETHİOPİA - Gebreyesus, Samuel Atsibha (PEARSON JOURNAL, 2022)
Budget is an important component in county government planning and decision making. A budget is the quantitative expression of a proposed plan of action by management for a specified period and aid to coordinating what needs to be done to implement the plan. A budget system that functions well is important to develop sustainable fiscal policies and economic growth. In many countries economic problems are worsen by weak budget systems and faulty budget choices. In developing countries, budgetary institutions are in their infancy and are mainly used as tools for legalistic controls and micromanagement. The general objective of the study was to evaluate factors affecting the effectiveness of budget management in the ministry of finance and economic cooperation of Ethiopia. To conduct the study both primary and secondary data were used. The primary data were collected from the ministry of finance and economic cooperation using questionnaire and interviews. SPSS 23 versions were used to analyze the collected data. The findings show that budget experts’ staff competency has strong impact on the budget management, to this end the ministry has put in place a training and development policy and arranged trainings programs to enhance budget experts’ skills; however, there is still a problem with ministry salary scale to attracts and retains qualified and experienced experts. Government budget laws and regulations have significant effect on the government budget management; the ministry has weaknesses in updating and revising the budget laws and regulations. Regarding the applications of IFMIS the Ministry prepares and executes the budget using IFMIS; however, it has still a room for the improvement of personnel with requisite knowledge & expertise for the effective implementation, operation, & maintenance of IFMIS. The ministry should strictly hold accountable the heads of line ministries for the breach of budget laws and regulations, it should provide trainings on the government budget management, public financial management and government accounting system to the public accounts standing committees of the legislative organs.